Development of a UPLC-FLD Method for Detection of Aflatoxin B1 and M1 in Animal Tissue to Study the Effect of Curcumin on Mycotoxin Clearance Rates - Cui, Xiaoxu; Muhammad, Ishfaq; Li, Rui; Jin, Huiran; Guo, Zhaolin; Yang, Yuqi; Hamid, Sattar; Li, Jiarui; Cheng, Ping; Zhang, Xiuying (Frontiers in Pharmacology, 2017)
Aflatoxin B1 (AFB1) and its metabolite aflatoxin M1 (AFM1) are well-known carcinogens for humans and animals health. In this study, an ultra-high performance liquid chromatography linked with fluorescence detection (UPLC-FLD) method was optimized and validated. In addition, we investigated for the first time, the influence of curcumin on residue depletion of AFB1 and AFM1 in liver, kidney and muscle tissues of broiler chickens and estimated a necessary clearance time required for AFB1 and AFM1 residues. The results showed that the average recoveries of AFB1 varied in liver, kidney and muscles between 82.32-85.56%, 85.34-88.45% and 84.88-89.73% respectively, while the average recoveries of AFM1 in liver, kidney and muscles varied between 92.17-95.03%, 94.12-97.21% and 95.32-98.51%, respectively. The detection limit of aflatoxin B1 was 0.008 ng/ml, while for aflatoxin M1 was 0.003 ng/ml. The limit of quantification for AFB1 and AFM1 was 0.02 ng/ml and 0.01 ng/ml, respectively. Clearance time for AFB1 and AFM1 residues were analyzed in two experimental groups of broilers. One group fed with dietary AFB1 (5.0 mg/kg feed) and other with curcumin+AFB1 diet (curcumin; 300 mg/kg feed, AFB1; 5.0 mg/kg feed). AFB1 and AFM1 residues clearance time was calculated based on limit of quantification (LOQ) using withdrawal time calculation software (WT1.4). Clearance time analyzed for AFB1 ranged from 11 to 19 days and for AFM1 ranged from 10 to 12 days at 95% confidence level. Interestingly, curcumin supplementation in the diet reduced the clearance time of AFM1 in liver and kidney but not in muscle tissues. Conclusively, the developed method can be appropriately used for the quality control testing of commercial broiler-meat processing companies, food manufacturers and quality control laboratories.